2021 IEEE 2nd International Conference on Big Data, Artificial Intelligence and Internet of Things Engineering (ICBAIE 2021) - Haoxuan Yu; Shuai Li (Proceedings, 2021)
On 27 March 2021, the 2021 IEEE 2nd International Conference on Big Data, Artificial Intelligence and Internet of Things Engineering (ICBAIE 2021) was officially held in Nanchang, China. The Conference invited the IEEE Fellow Professor Guo Yong-xin from the National University of Singapore and the IET Fellow Professor Gao Liang from Huazhong University of Science and Technology of China, as well as other experts, to make the special speeches. The conference focused on the practical application of big data, the development of artificial intelligence and the innovation of Internet of things technology, and the conference provided a platform for academic exchanges among experts and, the experts present reported their own research progress and made prospects for the future development of big data such as application of big data in enterprise decision making, artificial intelligence such as intelligent endoscope in medicine, Internet of Things such as the Internet of Vehicles in urban transport.